English Language Education in Thailand: What Should Be Done - Thadphoothon, Janpha; Isarankura, Soisithorn (วารสารมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏเชียงใหม่, 2023)
This paper addresses the challenges facing English language education in Thailand and offers practical solutions to improve its quality. The authors begin by analyzing the current state of English education in the formal context and identifying areas of weakness. Through their analysis and experience as English teachers, they propose ways to enhance the quality of English language education in Thailand. The authors acknowledge that improving English education in Thailand is a formidable task, but one that is worth undertaking. The paper provides valuable insights and recommendations for educators, policymakers, and other stakeholders in the field of English language education in Thailand.